GROWTH RESPONSE OF Pennisetum purpureum, Setaria spacelata AND Panicum maximum IN SALINITY - Sawen, Diana; Nuhuyanan, Lamberthus (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak; Vol 10 No 1 (2020): Pastura Vol 10 No. 1 Tahun 2020, 2020)
The study was conducted to determine the response of the growth of 3 grasses species to salinity. The study was conducted for 3 months, at Kompleks Perumahan Dosen UNIPA Amban in Manokwari West Papua. The study was designed with a split plot design in to Completely Randomize design (CRD) 4x3 with 4 replications. As the main plot is grass species and the subplot is salinity based on growing media. Main plot is grass species (Sp) consisting of: Pennisetum purpureum (Sp1), Panicum maximum (Sp2) and Setaria spacelata (Sp3) and then subplot is growing media (M) consisting of: soil 100% (M0), soil 70% + 30% of sand (M1), soil 50% + 50% of sand (M2) and soil 30% + 70% of sand (M3). Statistical analysis shows that the effect of salinity is significant on plant growth variable, namely plant height, number of leaves and number of tiller in each grass species. Planting media M1(soil 70% + sand 30%) performs the best result, and species with positive response to salinity is Setaria grass (Sp3). Keywords: salinity, Pennisetum purpureum, Setaria spacelata, Panicum maximum